Economic and Health Challenges During and Post COVID-19 in the Global South - Ragab, Ingy Gamal (The Arab Journal of Administration, 2025)
The Global South, with its diverse economic development and health profiles among its population, has been suffering from different degrees of public health problems and challenges. These challenges ranged from poor access to health services, poor distribution of resources, inequalities in health, and large out-of-pocket spending. The challenges were intertwined and complicated with the new challenges triggered by the COVID-19 pandemic. This theoretical study aims to provide a comprehensive view of those challenges using secondary data sources that are used to compare the cases before and after the pandemic. The extracted data are used to analyze the various health and socioeconomic implications of COVID-19 in the Global South by focusing on the most vulnerable groups like children, women, and the informal employment. Some of the findings were represented using graphs, bar charts or tables. The results of the study indicate that most countries in the Global South suffered from weak healthcare systems prior to the pandemic which exacerbated the effects of the virus. In addition, there were secondary effects associated with COVID-19 either because of the prevention and containment measures taken to curb the virus or because of its economic consequences. Finally, the study provides recommendations and discusses opportunities that governments have if they are willing to build a more prepared and resilient health system for the future.